Pendidikan Inklusi Untuk Anak dengan Gangguan Emosi dan Perilaku ( Tunalaras) - Ali, Mahfudz; travelancya DP, Terza (LP3M UNZAH GENGGONG, 2020)
Abstrak Children with mental retardation are individuals who experience emotional and behavioral barriers, so they are less able or have difficulty in adjusting well to their environment and this will interfere with their learning situation. Therefore, it is necessary to hold proper education for them. The purpose of this study was to determine the appropriate education for children with emotional and behavioral disorders (tunalaras). This study uses a qualitative research method which is a research about research and is descriptive. So that the research results can be obtained in the form of: 1. understanding of children with mental retardation needs 2. Characteristics of children with intellectual disabilities 3. causes of mental retardation 4. Classification of children with mental retardation 5. Inclusive education for children with hearing impairment. Keywords: Tunalaras, Strategy, Classification